SPILLOVER EFFECT PEREKONOMIAN PROVINSI DKI JAKARTA DAN SUMATERA SELATAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI LAMPUNG - Suparta, I Wayan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
This study was based on 23-year period time series data from 1983 to 2005. An OLS method was applied to test the hypothesis that economic variables such as private investments, local government spending, prices of domestic goods, prices of goods and income of the adjacent regions (Jakarta and South Sumatera Province) have effects on the economic growth of Lampung Province. The results of this study show that the independent economic variables have significant effects on the economic growth of Lampung Province. It is found that the interregional linkage is important. A comparison of the two neighbor provinces shows that the linkage of Lampungâs economy with Jakartaâs economy is relatively stronger than that with South Sumatera Province. The implication of this study is that the provincial and local governments of Lampung as well as the people of Lampung should make better use of the spatial spillover effect of DKI Jakarta and South Sumatera Province.